2018
DOI: 10.3390/en11071785
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Optimization of Gradient Bandgap Structure for CIGS Solar Cell with ZnS Buffer Layer Using Technology Computer-Aided Design Simulation

Abstract: Abstract:The band structure characteristics of a copper indium gallium sulfur selenide (Cu(In 1-x Ga x )SeS, CIGS) solar cell incorporating a cadmium-free zinc sulfide (ZnS) buffer layer were investigated using technology computer-aided design simulations. Considering the optical/electrical properties that depend on the Ga content, we numerically demonstrated that the front gradient bandgap enhanced the electron movement over the band-offset of the ZnS interface barrier, and the back gradient bandgap generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The resulting current can be considered as the sum of the shortcircuit current Isc, originated from the photon absorption process. The current density is as follows [9]:…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The resulting current can be considered as the sum of the shortcircuit current Isc, originated from the photon absorption process. The current density is as follows [9]:…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The temperature for all simulations is set at 300 K. The parameters presented in Table 1 are in the same range as those seen in the literature [11,12]. The values of the electron and hole mobilities (µe and µh, respectively) could be considered overestimated, although in the contributions presented previously [12,13], the values of the mobilities for both carrier types are even higher (µe = 100 and µh = 25 cm 2 /V•s). Figure 3 introduces a second model that is relevant for the scope of this work.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical simulations can also be used to study new materials for CIGS devices. In reference [13], bandgap gradient optimization of CIGS devices with ZnS buffer layer was performed. The main result presented in reference [13] is how the bandgap gradient in CIGS affects the carrier transportation, and in turn the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have highlighted the positive influence of band gap profiling in CIGS structures on the generation and collection of minority carriers. Lafuente-Sampietro et al studied the impact of double grading on the charge-carrier transport of a CIGS-based PV cell. It is shown that by a judicious choice of the notch position of the conduction band, the double grading allows benefiting from the advantages of both front grading and back grading. , An efficiency of 19.83% was recorded for a 2 μm thick absorber coat.…”
Section: Introductionmentioning
confidence: 99%